Production, identification, in silico analysis, and cytoprotection on H2O2-induced HUVECs of novel angiotensin-I-converting enzyme inhibitory peptides from Skipjack tuna roes - Zhu, Wang-Yu; Wang, Yu-Mei; Ge, Ming-Xue; Wu, Hua-Wei; Zheng, Shuo-Lei; Zheng, Huai-Yu; Wang, Bin (Frontiers in Nutrition, 2023)
This study was to identify the angiotensin-I-converting enzyme (ACE) inhibitory (ACEi) peptides from roe hydrolysate of Skipjack tuna (Katsuwonus pelamis) and evaluate their protection functions on H2O2-induced human umbilical vein endothelial cells (HUVECs). Therefore, protein hydrolysate of tuna roes with high ACEi activity was prepared using flavourzyme, and four ACEi peptides with significant activity were isolated from the hydrolysate and identified as WGESF, IKSW, YSHM and WSPGF, respectively. The affinity of WGESF (TRP3), IKSW (TRP6), YSHM (TRP9) and WSPGF (TRP12) with ACE was -8.590, -9.703, -9.325 and -8.036 kcal/mol, respectively. The molecular docking experiment elucidated that the significant ACEi ability of WGESF (TRP3), IKSW (TRP6), YSHM (TRP9) and WSPGF (TRP12) was mostly owed to their tight bond with ACE’s active sites/pockets via hydrophobic interaction, electrostatic force and hydrogen bonding. Additionally, WGESF (TRP3), IKSW (TRP6), YSHM (TRP9) and WSPGF (TRP12) could dramatically elevate the Nitric Oxide (NO) production and bring down endothelin-1 (ET-1) secretion in HUVECs, but also abolish the opposite impact of norepinephrine (0.5 μM) on the production of NO and ET-1. Moreover, WGESF (TRP3), IKSW (TRP6), YSHM (TRP9) and WSPGF (TRP12) could lower the oxidative damage and apoptosis rate of H2O2-induced HUVECs, and the mechanism indicated that they could increase the content of NO and activity of superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) to decrease the generation of reactive oxygen species (ROS) and malondialdehyde (MDA). Therefore, WGESF (TRP3), IKSW (TRP6), YSHM (TRP9) and WSPGF (TRP12) are beneficial ingredients for healthy products ameliorating hypertension and cardiovascular diseases.